Performance of Public Universities in Pakistan: Mediating Role of Cultural Factors - ISLAM, DEWAN MD. ZAHURUL; KHALID, NADEEM; ARSHAD, IMRAN (The journal of contemporary issues in business and government, 2021)
The main objective of the current research is to assess the mediating role of organisational cultural between entrepreneurial orientation, structural factor and performance of public universities. The contribution of universities in the development of any country is an undeniable fact. The previous studies emphasised on such aspects, as structural factors that affect universities performance but the role of cultural factors have been ignored. The current study explores cultural factors as mediating variable between structural factors, entrepreneurial factors and performance of public universities. The current research applied a combination of qualitative and quantitative methods. We developed, through an in-depth desktop research, a questionnaire that was distributed by mailed/postal survey to the randomly selected 415 respondents working in Pakistani public universities. The collected data was analysed using structural equation modelling (SEM) with the help of SmartPLS 3.2.7, a widely used data analytical tool. Out study finds that cultural factors significantly mediate the relationship between structural factors, entrepreneurial factors and performance of public universities. The university management at different level is expected to enhance competencies of conducting high quality teaching, research and contribution to wider society through utilisation of scarce resources and creating a congenial cultural environment to maximize outcome from the available strength and opportunities and overcome the weakness and challenges. The findings and recommendations are expected to add value to the current body of literature in the higher education and particular value addition will be for the Pakistani universities.